Different Hazards, Different Responses: Assessments of Flooding and COVID-19 Risks among Upstate New York Residents. (January 2022) - Zinda, John Aloysius; Zhang, James; Williams, Lindy B.; Kay, David L.; Alexander, Sarah M.; Zemaitis, Libby
The coronavirus disease 2019 (COVID-19) pandemic and extreme flooding events have recently taken enormous tolls. Drawing on research into differential risk responses across hazards, the authors examine how different social processes surrounding risk from flooding and COVID-19 shape how people respond to each hazard. Data from a household survey of 498 residents in two cities in the northeastern United States reveal that levels of concern and protective measures vary across the two hazards. Whereas climate polarization does not appear to influence flood risk responses, COVID-19 responses appear strongly polarized. However, having a known risk condition can offset Republicans' doubts about COVID-19. In addition, whereas people of color express greater concern about flooding, white people take more protective measures, and women are more likely than others to take protective measures against COVID-19. Contrasting stakes, immediacy, dread, and polarization surrounding flooding and COVID-19 intersect with social inequalities to produce differing patterns of risk response.